Nuclear LSm8 affects number of cytoplasmic processing bodies via controlling cellular distribution of Like-Sm proteins - Novotny, Ivan; Podolská, Katerina; Blazíková, Michaela; Valásek, Leos Shivaya; Svoboda, Petr; Stanek, David (Molecular biology of the cell, 2012)
Processing bodies (P-bodies) are dynamic cytoplasmic structures involved in mRNA degradation, but the mechanism that governs their formation is poorly understood. In this paper, we address a role of Like-Sm (LSm) proteins in formation of P-bodies and provide evidence that depletion of nuclear LSm8 increases the number of P-bodies, while LSm8 overexpression leads to P-body loss. We show that LSm8 knockdown causes relocalization of LSm4 and LSm6 proteins to the cytoplasm and suggest that LSm8 controls nuclear accumulation of all LSm2-7 proteins. We propose a model in which redistribution of LSm2-7 to the cytoplasm creates new binding sites for other P-body components and nucleates new, microscopically visible structures. The model is supported by prolonged residence of two P-body proteins, DDX6 and Ago2, in P-bodies after LSm8 depletion, which indicates stronger interactions between these proteins and P-bodies. Finally, an increased number of P-bodies has negligible effects on microRNA-mediated translation repression and nonsense mediated decay, further supporting the view that the function of proteins localized in P-bodies is independent of visible P-bodies.
Keywords: Autoantigens; cytoplazmatická granula; N-terminální acetyltransferasa C; Microscopy, Fluorescence; Ribonucleoproteins, Small Nuclear; lidé; Recombinant Fusion Proteins; Humans; protoonkogenní proteiny; Proto-Oncogene Proteins; proteiny vázající RNA; ribonukleoproteiny malé jaderné; autoantigeny; RNA Processing, Post-Transcriptional; transport proteinů; Cell Nucleus; N-Terminal Acetyltransferase C; rekombinantní fúzní proteiny; DEAD-box RNA Helicases; posttranskripční úpravy RNA; Ribonucleoprotein, U4-U6 Small Nuclear; buněčné jádro; Cytoplasmic Granules; malý jaderný ribonukleoprotein U4-U6; Protein Transport; DEAD-box RNA-helikasy; RNA-Binding Proteins; fluorescenční mikroskopie